2016
DOI: 10.1016/j.jbiomech.2015.12.047
|View full text |Cite|
|
Sign up to set email alerts
|

Correlations between measures of dynamic balance in individuals with post-stroke hemiparesis

Abstract: Mediolateral balance control during walking is a challenging task in post-stroke hemiparetic individuals. To detect and treat dynamic balance disorders, it is important to assess balance using reliable methods. The Berg Balance Scale (BBS), Dynamic Gait Index (DGI), margin-of-stability (MoS), and peak-to-peak range of angular-momentum (H) are some of the most commonly used measures to assess dynamic balance and fall risk in clinical and laboratory settings. However, it is not clear if these measures lead to si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
64
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 34 publications
2
64
0
Order By: Relevance
“…The results pointing out that elderly F prioritize a more stable strategy than NF at FO could be interpreted as a poorer control of balance and an increased risk of fall. It has recently been suggested that an increased MoS is an indicator of a decreased control of lateral balance and a higher risk of fall during gait (Vistamehr et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…The results pointing out that elderly F prioritize a more stable strategy than NF at FO could be interpreted as a poorer control of balance and an increased risk of fall. It has recently been suggested that an increased MoS is an indicator of a decreased control of lateral balance and a higher risk of fall during gait (Vistamehr et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Angular momentum can also capture balance impairments in populations with gait asymmetries and sensorimotor deficits such as amputees and stroke survivors. These individuals often have a higher peak-to-peak range of angular momentum than healthy controls [1316], and the presence of gait asymmetries may contribute to balance impairments in these populations. For example, the magnitude of step length asymmetry in people-post stroke is negatively correlated with scores on the Berg Balance Scale, indicating that step length asymmetry is associated with increased fall risk [17].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on dynamic balance control demonstrated that the paretic side had a weaker response to perturbations (de Kam, Kamphuis, Weerdesteyn, & Geurts, 2017), and that mediolateral gait instability was greater (Kao, Dingwell, Higginson, & Binder-Macleod, 2014) in poststroke people compared with healthy individuals. Other studies have investigated correlations between clinical scores and laboratory-based measures, including marginof-stability (Vistamehr, Kautz, Bowden, & Neptune, 2016) and whole-body angular momentum (Nott, Neptune, & Kautz, 2014), and examined the effect of visual feedback on gait in individuals with chronic stroke (Walker, Hyngstrom, & Schmit, 2016). However, it is unclear how individuals with hemiparesis adapt to accommodate both the major direction of motion (anteroposterior or vertical) and the mediolateral direction that is inherently unstable for them.…”
mentioning
confidence: 99%